Black footballers in Britain - Sarpong, A. (2002)
It was not until the late 1970s that the number of black players within the professional ranks of British football gradually began to increase to significant numbers. This marked the real beginnings of a significant breakthrough which was to lead to the game in Britain becoming more ethnically diverse, although racism in football during the seventies and eighties became a serious social problem. However, it would be wrong to suggest that the history of black players within the British game can be traced back only to the late sixties. There has actually been a small and largely unacknowledged black contingent in the British game since the formative years of competitive professional football in Britain. The article reviews the time before the first World War, the inter-war years, the post-war years - 1946 to the early 1960s, the 1970s and early 1980s: a "black explosion" and the late 1980s and the 1990s. It is also asked: Asians can't play football?